No association between apolipoprotein E or N‐Acetyltransferase 2 gene polymorphisms and age‐related hearing loss - Dawes, Piers (Laryngoscope, 2014)
OBJECTIVES/HYPOTHESIS: Age‐related hearing loss has a genetic component, but there have been limited genetic studies in this field. Both N‐acetyltransferase 2 and apolipoprotein E genes have previously been associated. However, these studies have either used small sample sizes, examined a limited number of polymorphisms, or have produced conflicting results. Here we use a haplotype tagging approach to determine association with age‐related hearing loss and investigate epistasis between these two genes. STUDY DESIGN: Candidate gene association study of a continuous phenotype. METHODS: We investigated haplotype tagging single nucleotide polymorphisms in the N‐acetyltransferase 2 gene and the presence/absence of the apolipoprotein E ε4 allele for association with age‐related hearing loss in a cohort of 265 Caucasian elderly volunteers from Greater Manchester, United Kingdom. Hearing phenotypes were generated using principal component analysis of the hearing threshold levels for the better ear (severity, slope, and concavity). Genotype data for the N‐acetyltransferase 2 gene was obtained from existing genome‐wide association study data from the Illumina 610‐Quadv1 chip. Apolipoprotein E genotyping was performed using Sequenom technology. Linear regression analysis was performed using Plink and Stata software. RESULTS: No significant associations (P value, > 0.05) were observed between the N‐acetyltransferase 2 or apolipoprotein E gene polymorphisms and any hearing factor. No significant association was observed for epistasis analysis of apolipoprotein E ε4 and the N‐acetyltransferase 2 single nucleotide polymorphism rs1799930 (NAT2*6A). CONCLUSION: We found no evidence to support that either N‐acetyltransferase 2 or apolipoprotein E gene polymorphisms are associated with age‐related hearing loss in a cohort of 265 elderly volunteers. LEVEL OF EVIDENCE: N/A. Laryngoscope, 125:E33–E38, 2015